â€œAl-Musaqahâ€ and Sharia Agribusiness System: An Alternative Way to Meet Staple Food Self-Sufficiency in Contemporary Indonesia - Maman, Ujang Maman; Kusmana, Kusmana; Supiandi, Dudi (Hunafa: Jurnal Studia Islamika, 2017)
The concept of al-musaqah appears in Islamic history when Prophet Muhammad conquered the fertile farmland surrounding Khaibar, abandoned by Jews as the original owner of the land. The concept of al-musaqoh also appears in fiqh deliberations, in which it is a partnership between tenants and land owners. By deepening literature, the concept of al-musaqah is part of sharia agribusiness system that could be an alternative partnerships and farmer institution in meeting staple food needs. The alternative concept is very necessary since Indonesia has been facing the issue of agricultural land conversion and difficulty to form sustainable food agriculture area (SFAA). For the implementation of al-musaqoh, the Government should systematically form the SFAA on the state owned land, and estabilish its institution to manage SFAA in the central and regional level. Then, the SFAA management implement al-musaqoh partnership with farmer groups. By the concept, the Government would be able to control staple food procurement and distribution to achieve food self-sufficiency which is profitable for farmers and non-farmers. However, the implementation is based on the view that the provision of basic needs should not be left to market mechanism.